Perancangan Buku Pedoman Pintar Berdoa Berbasis Karikatur di SD Negeri 03 Simpang Utara Kecamatan Simpang Alahan Mati Kabupaten Pasaman - Chintia Azella; Zulfani Sesmiarni (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to design and test the feasibility of a caricature-based smart prayer guidebook as a supporting medium for Islamic Religious Education learning in elementary schools. The background of this study is the need for teachers to have media that is interesting, communicative, and appropriate to the characteristics of elementary school-aged students in instilling the habit of praying. The method used is Research and Development (R&D) with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Data collection instruments include expert validation sheets, teacher response questionnaires, and documentation. The results of the study indicate that the developed guidebook has a high level of feasibility, with a validity value of 0.86, practicality of 1.00, and effectiveness of 0.92. In addition, teacher responses to the use of this book are very positive.